2014
DOI: 10.1038/srep05158
|View full text |Cite
|
Sign up to set email alerts
|

Zn vacancy induced green luminescence on non-polar surfaces in ZnO nanostructures

Abstract: Although generally ascribed to the presence of defects, an ultimate assignment of the different contributions to the emission spectrum in terms of surface states and deep levels in ZnO nanostructures is still lacking. In this work we unambiguously give first evidence that zinc vacancies at the (1010) nonpolar surfaces are responsible for the green luminescence of ZnO nanostructures. The result is obtained by performing an exhaustive comparison between spatially resolved cathodoluminescence spectroscopy and ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
106
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 52 publications
25
106
2
Order By: Relevance
“…An enhancement in the UV peak intensity occurs only when radiative and/or non-radiative defect centers within the band gap are reduced. Green emission is the most notorious one affecting the intensity of the UV emission and the former being caused by the Zn vacancy (V Zn ) defects [54][55][56][57]. In our Sn doped films, some Sn 4+ ions are probably causing charge compensation by making a complex with V Zn [37].…”
Section: Electrical and Photoluminescence Propertiesmentioning
confidence: 96%
“…An enhancement in the UV peak intensity occurs only when radiative and/or non-radiative defect centers within the band gap are reduced. Green emission is the most notorious one affecting the intensity of the UV emission and the former being caused by the Zn vacancy (V Zn ) defects [54][55][56][57]. In our Sn doped films, some Sn 4+ ions are probably causing charge compensation by making a complex with V Zn [37].…”
Section: Electrical and Photoluminescence Propertiesmentioning
confidence: 96%
“…In the visible emission spectrum, different defects are attributed to the green, yellow, and orange-red emissions [16,27]. The green emission band is attributed to a variety of defects including singly ionised oxygen vacancies [28][29][30][31], antisite oxygen [17,32,33], zinc interstitials [34], and zinc vacancies [35]. Given that there is no consensus in the mechanism for green emission, this shows how highly debated the origins of the luminescence are for ZnO [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…However, with regard to nanostructured ZnO, Djurišić et al 8 and Fabbri et al 17 19 reported that the DLE arises mainly from surface layer, whereas Chang et al 20 have suggested that it originates from the bulk. We assume that this disagreement could be associated with the penetration depth of the excitation light for the specific ZnO nanostructures, in which the defect states vary with the depth.…”
Section: Resultsmentioning
confidence: 95%